A persuasive agent architecture for behavior change intervention - Adegoke Ojeniyi; Adam Khalid; Obafunmiso Christiana Kehinde (International Journal of Informatics and Communication Technology (IJ-ICT), 2022)
A persuasive agent makes use of persuasion attributions to ensure that its predefined objective(s) is achieved within its immediate environment. This is made possible based on the five unique features namely sociable, persuasive, autonomy, reactive, and proactive natures. However, there are limited successes recorded within the behavioural intervention and psychological reactance is responsible for these failures. Psychological reactance is the stage where rejection, negative response and frustration are felt by the users of the persuasive system. Thus, this study proposes a persuasive agent (PAT) architecture that limits the experience of psychological reactance to achieve an improved behavioural intervention. PAT architecture adopted the combination of the reactance model for behavior change and the persuasive design principle. The architecture is evaluated by conducting an experimental study using a user-centred approach. The evaluation reflected that there is a reduction in the number of users who experienced psychological reactance from 70 per cent to 3 per cent. The result is a better improvement compared with previous outcomes. The contribution made in this study would provide a design model and a steplike approach to software designers on how to limit the effect of psychological reactance on persuasive system applications and interventions.